Preparation method and application of MXene-based asymmetric all-solid-state supercapacitor electrode material
The preparation of MXene-based asymmetric all-solid-state supercapacitor electrode material through multi-step hydrothermal method solves the problems of low energy density and fast specific capacity decay, and achieves high energy density and good cycling performance.
Patent Information
- Application Number
- CN202411030411.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-07-30
AI Technical Summary
When MXene electrode materials are used in supercapacitors, there are problems such as low energy density and rapid specific capacity attenuation, which limits its application.
Multi-step hydrothermal method is used to prepare MXene-based asymmetric all-solid supercapacitor electrode materials, including the preparation of Ti3C2, the formation of potassium ion intercalation, the addition of DMSO intercalation, and MnO2 coating. These steps are used to improve the conductivity and ion transport capability of the electrode materials.
It achieves high energy density, good long cycle performance and high rate performance, and is suitable for asymmetric all-solid-state supercapacitors.
Smart Images

Figure CN118919317B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of all-solid-state supercapacitors, and in particular to a preparation method and application of a MXene-based asymmetric all-solid-state supercapacitor electrode material. Background Art
[0002] As a new type of energy storage container, supercapacitors have ultra-high power density, fast charge and discharge efficiency, good cycle stability and a wide operating temperature range compared to traditional energy storage devices such as batteries and fuel cells. The basic structure of supercapacitors includes electrodes, electrolytes, current collectors, diaphragms and shells. Its energy storage is generated by the accumulation of charges by active substances in electrode materials. Therefore, it is very important to develop electrode materials with high specific capacity and high conductivity.
[0003] At present, the electrode materials used in supercapacitors are often mainly carbon materials. Among them, MXene materials have great application potential in the fields of portable electronic products, electric vehicles, and energy storage devices due to their unique layered structure, high specific surface area, rich controllable surface functional groups, and excellent conductivity. However, MXene electrode material supercapacitors still have problems such as low energy density and too fast specific capacity decay, which seriously limit the application of MXene electrode material supercapacitors. Therefore, it is urgent to develop a MXene electrode material that enables supercapacitors to have high energy density, good long cycle performance, and high rate performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a preparation method and application of a MXene-based asymmetric all-solid-state supercapacitor electrode material. The preparation method is simple and reasonable, easy to operate, and can be used as an asymmetric all-solid-state supercapacitor electrode material to enable the supercapacitor to have the advantages of high energy density, good long cycle performance and high rate performance.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a MXene-based all-solid-state supercapacitor electrode material comprises the following steps:
[0007] (1) Preparation of Ti3C2
[0008] The precursor Ti3AlC2 powder is placed in a HCl / NH4F mixed solution and magnetically stirred at 50-70°C for 12-24h. The suspension after the reaction is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain Ti3C2.
[0009] (2) Preparation of potassium ion intercalated Ti3C2
[0010] The Ti3C2 obtained in step (1) is dissolved in a KOH solution and stirred at 60-70°C for 5-8 hours. The obtained suspension is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain potassium ion intercalated Ti3C2 (K-Ti3C2);
[0011] (3) Preparation of DMSO-potassium ion intercalated Ti3C2
[0012] The potassium ion intercalated Ti3C2 obtained in step (2) is mixed with DMSO and stirred at 60-70°C for 3-5 hours. The obtained suspension is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2);
[0013] (4) Preparation of MnO2@DK-Ti3C2
[0014] The DMSO-potassium ion intercalated Ti3C2 obtained in step (3) is dissolved in a 0.1-0.5M KMnO4 solution, and the mixed solution is reacted at 120-180°C for 5 hours. The suspension after the reaction is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain manganese dioxide-coated DMSO-potassium ion intercalated Ti3C2 (MnO2@DK-Ti3C2) powder.
[0015] Furthermore, in step (1), the molar ratio of HCl to NH4F is 3:2, and the concentration of HCl is 8 mol·L -1 ~10mol·L -1 The volume of the HCl / NH4F mixed solution is 20 mL, and the mass volume ratio of the precursor Ti3AlC2 to the HCl / NH4F mixed solution is 1:20 g·mL -1 .
[0016] Furthermore, the speed of magnetic stirring in step (1) is 300 to 500 rpm·min -1 , centrifugal speed is 3000~4000rpm·min -1 , washing with deionized water until the pH value of the suspension is 6-7; the speed of magnetic stirring in step (2) is 300-500 rpm·min -1 , washed with deionized water until the pH of the suspension is 6-7, and the centrifugal speed is 3000-4000 rpm·min -1 Step (3) The speed of magnetic stirring is 300 to 500 rpm min -1 , washing with deionized water for 6 to 7 times until the suspension becomes transparent, and the centrifugal speed is 3000 to 4000 rpm min -1In step (4), the centrifugal speed is 3000-4000 rpm min -1 , wash with deionized water until the pH of the suspension is 6-7, wash the suspension until it is transparent, dry at 60-80°C, and dry for 8-12h.
[0017] Furthermore, the concentration of the KOH solution is 2 to 3 mol·L -1 The mass volume ratio of Ti3C2 to KOH solution is 1:30 g·mL -1 .
[0018] Furthermore, the mass volume ratio of potassium ion intercalated Ti3C2 and DMSO is 1:20 g / mL.
[0019] Furthermore, the concentration of KMnO4 is 0.1-0.5M, and the mass volume ratio of DMSO-potassium ion intercalated Ti3C2 to KMnO4 solution is 1:20g·mL -1 .
[0020] Furthermore, a MXene-based asymmetric all-solid-state supercapacitor electrode material prepared by the above-mentioned preparation method is used as an all-solid-state supercapacitor electrolyte additive and electrode material.
[0021] Furthermore, DMSO-potassium ion intercalated Ti3C2 was used as an electrolyte additive for all-solid-state supercapacitors, and its addition amount accounted for 20% of the total mass of the electrolyte.
[0022] Further, the specific steps are as follows:
[0023] (1) Preparation of positive electrode sheet
[0024] Manganese dioxide-coated DMSO-potassium ion intercalated Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet;
[0025] (2) Preparation of negative electrode sheet
[0026] The DMSO-potassium ion intercalated Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a negative electrode sheet;
[0027] (3) Preparation of solid electrolyte
[0028] Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and DMSO-potassium ion intercalated Ti3C2 was added as an additive, wherein the DMSO-potassium ion intercalated Ti3C2 accounted for 25% of the total mass of Li2S, P2S5, and LiCl, and the mixture was sintered in a vacuum furnace at 500°C for 5h. After cooling, Li with DK-Ti3C2 as an additive was obtained. 5.6 PS 4.6 Cl 1.4 Solid electrolytes;
[0029] (4) Assembly of asymmetric all-solid-state supercapacitors
[0030] The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor.
[0031] The beneficial technical effects of the present invention are:
[0032] (1) The present invention synthesizes a DK-Ti3C2 material with a wrinkled accordion shape through a three-step hydrothermal method of "etching-alkalization-intercalation". The surface functional groups of Ti3C2 are regulated by KOH solution, thereby reducing the interaction force between the surface -F functional groups and ions, thereby increasing the diffusion rate of ions in the transmission channel. Under the intercalation effect of ions and organic molecules, DK-Ti3C2 has a larger ion transmission channel. At the same time, the presence of the intercalant solves the self-stacking phenomenon between DK-Ti3C2 sheets after ion deintercalation, ensuring efficient ion transmission. The DK-Ti3C2 electrode was electrochemically tested in a three-electrode system in a KOH electrolyte, and the results showed that at 5Ag -1 It can provide up to 300Fg at a current density of -1 The specific capacity can still provide 240Fg at a current density of 10A / g. -1 The specific capacity and rate performance are as high as 80%. It is an ideal asymmetric all-solid-state supercapacitor negative electrode material;
[0033] (2) The MnO2@DK-Ti3C2 composite material prepared by the in-situ composite hydrothermal method of the present invention is characterized by a DK-Ti3C2 matrix coated with flower-ball-shaped MnO2; due to the strong redox activity of MnO2, the composite material has a high ion adsorption efficiency, thus having a large energy density; at the same time, under the synergistic effect of the DK-Ti3C2 matrix, the number of free electrons inside MnO2 is increased by constructing a stable electron transmission channel, thereby improving the transmission rate of ions inside MnO2. The MnO2@DK-Ti3C2 electrode was subjected to electrochemical testing under a three-electrode system in a KOH electrolyte, and the results showed that at 5Ag -1 It can provide up to 370Fg at a current density of -1The specific capacity of 10Ag -1 286Fg can still be provided at a current density of -1 The specific capacity and rate performance are as high as 77%. It is an ideal asymmetric all-solid-state supercapacitor positive electrode material; and it still has good capacitance retention rate in long-term charge and discharge cycles;
[0034] (3) The solid electrolyte prepared by the present invention is a PVA / KOH gel electrolyte with DK-Ti3C2 as an additive. By adding DK-Ti3C2 with good conductivity to the PVA / KOH gel electrolyte, the transmission rate of ions and electrons in the solid electrolyte can be increased, thereby improving the electrochemical performance of the all-solid-state supercapacitor.
[0035] The present invention increases the interlayer spacing of Ti3C2 by inserting a variety of ions and molecules into the interlayer of MXene, provides more adsorption and desorption active sites for ions in the solid electrolyte, enables the negative electrode material DK-Ti3C2 to store more ions, and the presence of interlayer intercalants improves the sub-stacking phenomenon of Ti3C2, so that it has good cycle stability performance, thereby improving the cycle life of the negative electrode material. By re-regulating the surface functional groups, the matrix Ti3C2 has more excellent conductivity. By using DK-Ti3C2 as the matrix material, in-situ composite generation of the coating structure MnO2@DK-Ti3C2, the pseudocapacitive properties of the surface-coated MnO2, the positive electrode material MnO2@DK-Ti3C2 has a greater energy density, and due to the presence of the matrix DK-Ti3C2, MnO2@DK-Ti3C2 has good conductivity to ensure the response process to charged ions under high current density, so that the positive electrode material has good rate performance. At the same time, the coating of MnO2 avoids the structural damage of the matrix DK-Ti3C2, giving it a good long cycle life. The two prepared electrode materials have reasonable positive and negative electrode capacity matching, as well as a solid electrolyte with good conductive properties, making the MnO2@DK-Ti3C2 / / DK-Ti3C2 asymmetric all-solid-state supercapacitor device have a wide range of application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The XRD spectra of (a) the etched product Ti3C2, the "alkalization-intercalation" product DK-Ti3C2, and (b) the composite product MnO2@DK-Ti3C2 in Example 1 of the present invention;
[0037] Figure 2 These are SEM images of (a) Ti3AlC2 precursor, (b) etching product Ti3C2, (c) alkalization-intercalation product DK-Ti3C2, and (d) composite product MnO2@DK-Ti3C2 in Example 1 of the present invention;
[0038] Figure 3 The first principle theoretical calculation and actual test results of the MnO2@DK-Ti3C2 composite material in Example 1 of the present invention are as follows: (a) differential charge density diagram, (b) two-dimensional slice differential density diagram, (c) state density diagram, and (d) EIS test diagram;
[0039] Figure 4 These are the GCD test results of (a) DK-Ti3C2 and (b) MnO2@DK-Ti3C2 composite materials in Example 1 of the present invention;
[0040] Figure 5 The capacity matching of the positive and negative electrode materials in Example 1 of the present invention;
[0041] Figure 6 It is the XRD spectrum and SEM picture of Ti3C2 prepared by using HCl / NaF as an etchant in Comparative Example 1 of the present invention;
[0042] Figure 7 It is the XRD spectrum and SEM picture of Ti3C2 prepared by using HCl / LiF as an etchant in Comparative Example 2 of the present invention;
[0043] Figure 8 The electrochemical test results of the product K-Ti3C2 in Comparative Example 4 of the present invention are shown in Figure 1. (a) is the GCD curve of K-Ti3C2 at different current densities, and (b) is the CV curve of K-Ti3C2 after 100 cycles.
[0044] Fig. 9 Schematic diagram of the assembled MnO2@DK-Ti3C2 / / DK-Ti3C2 asymmetric all-solid-state supercapacitor device. DETAILED DESCRIPTION
[0045] Example 1
[0046] (1) Preparation of Ti3C2
[0047] 1g of the precursor Ti3AlC2 powder was dissolved in 20mL of a HCl / NH4F mixed solution, wherein the molar ratio of HCl to NH4F in the HCl / NH4F mixed solution was 3:2 and the concentration of HCl was 9mol·L -1 , and at 60°C, at 400 rpm·min -1 The suspension was stirred at a stirring speed of 3000 rpm·min for 24 h. -1 The suspension was centrifuged at a centrifugal speed of , and then washed with deionized water until the pH value of the suspension was 7, vacuum filtered, and dried to obtain Ti3C2;
[0048] (2) Preparation of potassium ion intercalated Ti3C2:
[0049] Weigh 1g of Ti3C2 obtained in step (1) and dissolve it in 30mL of 3mol·L -1 KOH solution at 60°C and 400 rpm -1 The suspension was stirred at a stirring speed of 3000 rpm·min for 6 h. -1 The suspension was centrifuged at a centrifugal speed of 10000 nm, and then washed with deionized water until the pH value of the suspension was 7. After vacuum filtration, the suspension was dried to obtain Ti3C2 and potassium ion intercalated Ti3C2 (K-Ti3C2).
[0050] (3) Preparation of DMSO-potassium ion intercalated Ti3C2
[0051] Weigh 1 g of the potassium ion intercalated Ti3C2 (K-Ti3C2) obtained in step (2) and mix it with 20 mL of DMSO. -1 The suspension was stirred at a stirring speed of 3000 rpm for 5 h. -1 The suspension was centrifuged at a centrifugal speed and then washed with deionized water for 7 times. The suspension was transparent and then vacuum filtered and dried to obtain DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2).
[0052] (4) Preparation of MnO2@DK-Ti3C2
[0053] Weigh 1 g of the DMSO-potassium intercalated Ti3C2 obtained in step (3) and dissolve it in 20 mL of 0.5 M KMnO4 solution. The mixed solution is reacted at 150 °C for 5 h and then heated at 3000 rpm. -1 The suspension was washed with deionized water until the pH value of the suspension was 7, and the suspension was washed until transparent, and dried at 80°C for 12h to obtain manganese dioxide-coated DMSO-Ti3C2 (MnO2@DK-Ti3C2) powder;
[0054] (5) Assembly of MXene-based asymmetric all-solid-state supercapacitors
[0055] DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2) was used as the negative electrode material, manganese dioxide coated DK-Ti3C2 (MnO2@DK-Ti3C2) was used as the positive electrode material, and Li 5.6 PS 4.6 Cl 1.4 As a solid electrolyte, the specific production process is as follows:
[0056] Step 1: Preparation of MnO2@DK-Ti3C2 positive electrode sheet
[0057] MnO2@DK-Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet;
[0058] Step 2: Preparation of DK-Ti3C2 negative electrode sheet
[0059] The DK-Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a negative electrode sheet;
[0060] Step 3: Preparation of solid electrolyte
[0061] Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and DK-Ti3C2 was added as an additive, wherein the DK-Ti3C2 accounted for 25% of the total mass of Li2S, P2S5, and LiCl, and the mixture was sintered in a vacuum furnace at 500°C for 5h. After cooling, Li with DK-Ti3C2 as an additive was obtained. 5.6 PS 4.6 Cl 1.4 Solid electrolytes;
[0062] Step 4: Assembly of asymmetric all-solid-state supercapacitor
[0063] The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor.
[0064] Figure 1 The XRD patterns of the electrode materials DK-Ti3C2 and MnO2@DK-Ti3C2 were successfully prepared. Figure 2 It can be seen that this matrix DK-Ti3C2 has obvious sheet separation, thus presenting an accordion-like layered structure, providing more active sites for ions to store more charged ions. And this MnO2@DK-Ti3C2 has an obvious coating structure, which greatly improves the long cycle performance of the electrode material. Under the synergistic effect of the matrix Ti3C2, the conductivity of MnO2 is improved. Therefore, in the electrochemical test, MnO2@DK-Ti3C2 has good conductivity, such as Figure 3 The electrochemical test results under the three-electrode system are shown in Figure 4As shown in the figure, these two electrode materials MnO2@DK-Ti3C2 and DK-Ti3C2 can still provide large specific capacitance at high current density, indicating that they have large energy density and good rate performance. Figure 5 As shown, the two electrode materials have reasonable capacity matching characteristics.
[0065] Example 2
[0066] (1) Preparation of Ti3C2
[0067] 1g of the precursor Ti3AlC2 powder was dissolved in 20mL of a HCl / NH4F mixed solution, wherein the molar ratio of HCl to NH4F in the HCl / NH4F mixed solution was 3:2 and the concentration of HCl was 8mol·L -1 , and at 50°C, at 300 rpm·min -1 The suspension was stirred at a stirring speed of 3500 rpm·min for 12 h. -1 The suspension was centrifuged at a centrifugal speed of , and then washed with deionized water until the pH value of the suspension was 6, vacuum filtered, and dried to obtain Ti3C2;
[0068] (2) Preparation of potassium ion intercalated Ti3C2:
[0069] Weigh 1g of Ti3C2 obtained in step (1) and dissolve it in 30mL of 2mol·L -1 KOH solution at 70°C and 300 rpm -1 The suspension was stirred at a stirring speed of 3500 rpm·min for 6 h. -1 The suspension was centrifuged at a centrifugal speed of 10000 nm, and then washed with deionized water until the pH value of the suspension was 6. After vacuum filtration, the suspension was dried to obtain Ti3C2 and potassium ion intercalated Ti3C2 (K-Ti3C2).
[0070] (3) Preparation of DMSO-potassium ion intercalated Ti3C2
[0071] Weigh 1 g of the potassium ion intercalated Ti3C2 (K-Ti3C2) obtained in step (2) and mix it with 20 mL of DMSO. -1 The suspension was stirred at a stirring speed of 3500 rpm for 3 h. -1 The suspension was centrifuged at a centrifugal speed and then washed with deionized water for 7 times. The suspension was transparent and then vacuum filtered and dried to obtain DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2).
[0072] (4) Preparation of MnO2@DK-Ti3C2
[0073] 1 g of the DMSO-potassium intercalated Ti3C2 obtained in step (3) was weighed and dissolved in 20 mL of 0.3 M KMnO4 solution, and the mixed solution was reacted at 180 °C for 5 h and then heated at 3500 rpm min. -1 The suspension was washed with deionized water until the pH value of the suspension was 6, and the suspension was washed until transparent, and dried at 80°C for 12h to obtain manganese dioxide-coated DMSO-Ti3C2 (MnO2@DK-Ti3C2) powder;
[0074] (5) Assembly of MXene-based asymmetric all-solid-state supercapacitors
[0075] DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2) was used as the negative electrode material, manganese dioxide coated DK-Ti3C2 (MnO2@DK-Ti3C2) was used as the positive electrode material, and Li 5.6 PS 4.6 Cl 1.4 As a solid electrolyte, the specific production process is as follows:
[0076] Step 1: Preparation of MnO2@DK-Ti3C2 positive electrode sheet
[0077] MnO2@DK-Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet;
[0078] Step 2: Preparation of DK-Ti3C2 negative electrode sheet
[0079] The DK-Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a negative electrode sheet;
[0080] Step 3: Preparation of solid electrolyte
[0081] Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and DK-Ti3C2 was added as an additive, wherein the DK-Ti3C2 accounted for 25% of the total mass of Li2S, P2S5, and LiCl, and the mixture was sintered in a vacuum furnace at 500°C for 5h. After cooling, Li with DK-Ti3C2 as an additive was obtained. 5.6 PS 4.6 Cl 1.4 Solid electrolytes;
[0082] Step 4: Assembly of asymmetric all-solid-state supercapacitor
[0083] The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor. The assembled asymmetric all-solid-state supercapacitor has good electrochemical performance and application prospects.
[0084] Example 3
[0085] (1) Preparation of Ti3C2
[0086] 1g of the precursor Ti3AlC2 powder was dissolved in 20mL of a HCl / NH4F mixed solution, wherein the molar ratio of HCl to NH4F in the HCl / NH4F mixed solution was 3:2 and the concentration of HCl was 10mol·L -1 , and at 70°C, at 500 rpm·min -1 The suspension was stirred at a stirring speed of 4000 rpm·min for 18 h. -1 The suspension was centrifuged at a centrifugal speed of , and then washed with deionized water until the pH value of the suspension was 6, vacuum filtered, and dried to obtain Ti3C2;
[0087] (2) Preparation of potassium ion intercalated Ti3C2:
[0088] Weigh 1g of Ti3C2 obtained in step (1) and dissolve it in 30mL of 2mol·L -1 KOH solution at 60°C and 500 rpm -1 The suspension was stirred at a stirring speed of 4000 rpm·min for 8 h. -1 The suspension was centrifuged at a centrifugal speed of 10000 nm, and then washed with deionized water until the pH value of the suspension was 6. After vacuum filtration, the suspension was dried to obtain Ti3C2 and potassium ion intercalated Ti3C2 (K-Ti3C2).
[0089] (3) Preparation of DMSO-potassium ion intercalated Ti3C2
[0090] Weigh 1 g of the potassium ion intercalated Ti3C2 (K-Ti3C2) obtained in step (2) and mix it with 20 mL of DMSO. -1 The suspension was stirred at a stirring speed of 4000 rpm for 4 h. -1 The suspension was centrifuged at a centrifugal speed and then washed with deionized water for 6 times. The suspension was transparent and then vacuum filtered and dried to obtain DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2).
[0091] (4) Preparation of MnO2@DK-Ti3C2
[0092] Weigh 1 g of the DMSO-potassium intercalated Ti3C2 obtained in step (3) and dissolve it in 20 mL of 0.1 M KMnO4 solution. The mixed solution is reacted at 120 °C for 5 h and then heated at 4000 rpm min. -1 The suspension was washed with deionized water until the pH value of the suspension was 6, and the suspension was washed until transparent, and dried at 80°C for 12h to obtain manganese dioxide-coated DMSO-Ti3C2 (MnO2@DK-Ti3C2) powder;
[0093] (5) Assembly of MXene-based asymmetric all-solid-state supercapacitors
[0094] DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2) was used as the negative electrode material, manganese dioxide coated DK-Ti3C2 (MnO2@DK-Ti3C2) was used as the positive electrode material, and Li 5.6 PS 4.6 Cl 1.4 As a solid electrolyte, the specific production process is as follows:
[0095] Step 1: Preparation of MnO2@DK-Ti3C2 positive electrode sheet
[0096] MnO2@DK-Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet;
[0097] Step 2: Preparation of DK-Ti3C2 negative electrode sheet
[0098] The DK-Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a negative electrode sheet;
[0099] Step 3: Preparation of solid electrolyte
[0100] Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and DK-Ti3C2 was added as an additive, wherein the DK-Ti3C2 accounted for 25% of the total mass of Li2S, P2S5, and LiCl, and the mixture was sintered in a vacuum furnace at 500°C for 5h. After cooling, Li with DK-Ti3C2 as an additive was obtained. 5.6 PS 4.6 Cl 1.4Solid electrolytes;
[0101] Step 4: Assembly of asymmetric all-solid-state supercapacitor
[0102] The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor. The assembled asymmetric all-solid-state supercapacitor has good electrochemical performance and application prospects.
[0103] Comparative Example 1
[0104] (1) Preparation of Ti3C2
[0105] 1g of the precursor Ti3AlC2 powder was dissolved in 20mL of a HCl / NaF mixed solution, where the molar ratio of HCl to NH4F in the HCl / NaF mixed solution was 3:2 and the concentration of HCl was 9mol·L -1 , and at 60°C, 400 rpm -1 The suspension was stirred at a stirring speed of 1000 rpm for 24 h, and the reaction suspension was centrifuged at a centrifugal speed of 3000 rpm / min, then washed with deionized water until the pH value of the suspension was 7, vacuum filtered, and dried to obtain Ti3C2; the structure and micromorphology of the etched product were characterized as shown in Figure 6 shown; however Figure 6 The XRD spectrum and microscopic morphology SEM results of the etching product of Comparative Example 1 show that this etching product has a lower layer separation degree and cannot provide suitable adsorption active sites for ions;
[0106] (2) Preparation of potassium ion intercalated Ti3C2:
[0107] Weigh 1g of Ti3C2 obtained in step (1) and dissolve it in 30mL of 3mol·L -1 KOH solution at 60°C and 400 rpm -1 The suspension was stirred at a stirring speed of 3000 rpm·min for 6 h. -1 The suspension was centrifuged at a centrifugal speed of 10000 nm, and then washed with deionized water until the pH value of the suspension was 7. After vacuum filtration, the suspension was dried to obtain Ti3C2 and potassium ion intercalated Ti3C2 (K-Ti3C2).
[0108] (3) Preparation of DMSO-potassium ion intercalated Ti3C2
[0109] Weigh 1 g of the potassium ion intercalated Ti3C2 (K-Ti3C2) obtained in step (2) and mix it with 20 mL of DMSO. -1 The suspension was stirred at a stirring speed of 3000 rpm for 5 h.-1 The suspension was centrifuged at a centrifugal speed and then washed with deionized water for 7 times. The suspension was transparent and then vacuum filtered and dried to obtain DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2).
[0110] (4) Preparation of MnO2@DK-Ti3C2
[0111] Weigh 1 g of the DMSO-potassium intercalated Ti3C2 obtained in step (3) and dissolve it in 20 mL of 0.5 M KMnO4 solution. The mixed solution is reacted at 150 °C for 5 h and then heated at 3000 rpm. -1 The suspension was washed with deionized water until the pH value of the suspension was 7, and the suspension was washed until transparent, and dried at 80°C for 12h to obtain manganese dioxide-coated DMSO-Ti3C2 (MnO2@DK-Ti3C2) powder;
[0112] (5) Assembly of MXene-based asymmetric all-solid-state supercapacitors
[0113] DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2) was used as the negative electrode material, manganese dioxide coated DK-Ti3C2 (MnO2@DK-Ti3C2) was used as the positive electrode material, and Li 5.6 PS 4.6 Cl 1.4 As a solid electrolyte, the specific production process is as follows:
[0114] Step 1: Preparation of MnO2@DK-Ti3C2 positive electrode sheet
[0115] MnO2@DK-Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet;
[0116] Step 2: Preparation of DK-Ti3C2 negative electrode sheet
[0117] The DK-Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a negative electrode sheet;
[0118] Step 3: Preparation of solid electrolyte
[0119] Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and DK-Ti3C2 was added as an additive, wherein the DK-Ti3C2 accounted for 25% of the total mass of Li2S, P2S5, and LiCl, and the mixture was sintered in a vacuum furnace at 500°C for 5h. After cooling, Li with DK-Ti3C2 as an additive was obtained. 5.6 PS 4.6 Cl 1.4 Solid electrolytes;
[0120] Step 4: Assembly of asymmetric all-solid-state supercapacitor
[0121] The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor.
[0122] Comparative Example 2
[0123] (1) Preparation of Ti3C2
[0124] 1g of the precursor Ti3AlC2 powder was dissolved in 20mL of a HCl / LiF mixed solution, where the molar ratio of HCl to NH4F in the HCl / LiF mixed solution was 3:2 and the concentration of HCl was 9mol·L -1 , and at 60°C, 400 rpm -1 The suspension was stirred at a stirring speed of 3000 rpm·min for 24 h. -1 The product was centrifuged at a centrifugal speed and then washed with deionized water until the pH value of the suspension was 7. After vacuum filtration, it was dried to obtain Ti3C2. The structure and micromorphology of the etched product were characterized as follows: Figure 7 shown; Figure 7 The XRD spectrum and microscopic morphology SEM results of the etching product of Comparative Example 2 show that there are many by-products in the synthesis process of this etching product, and they are attached to the Ti3C2 layer, which hinders the adsorption and diffusion of ions during the electrochemical test, thereby affecting the electrochemical performance of the electrode material;
[0125] (2) Preparation of potassium ion intercalated Ti3C2:
[0126] Weigh 1g of Ti3C2 obtained in step (1) and dissolve it in 30mL of 3mol·L -1 KOH solution at 60°C and 400 rpm -1 The suspension was stirred at a stirring speed of 3000 rpm·min for 6 h. -1 The suspension was centrifuged at a centrifugal speed of 10000 nm, and then washed with deionized water until the pH value of the suspension was 7. After vacuum filtration, the suspension was dried to obtain Ti3C2 and potassium ion intercalated Ti3C2 (K-Ti3C2).
[0127] (3) Preparation of DMSO-potassium ion intercalated Ti3C2
[0128] Weigh 1 g of the potassium ion intercalated Ti3C2 (K-Ti3C2) obtained in step (2) and mix it with 20 mL of DMSO. -1 The suspension was stirred at a stirring speed of 3000 rpm for 5 h. -1 The suspension was centrifuged at a centrifugal speed and then washed with deionized water for 7 times. The suspension was transparent and then vacuum filtered and dried to obtain DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2).
[0129] (4) Preparation of MnO2@DK-Ti3C2
[0130] Weigh 1 g of the DMSO-potassium intercalated Ti3C2 obtained in step (3) and dissolve it in 20 mL of 0.5 M KMnO4 solution. The mixed solution is reacted at 150 °C for 5 h and then heated at 3000 rpm. -1 The suspension was washed with deionized water until the pH value of the suspension was 7, and the suspension was washed until transparent, and dried at 80°C for 12h to obtain manganese dioxide-coated DMSO-Ti3C2 (MnO2@DK-Ti3C2) powder;
[0131] (5) Assembly of MXene-based asymmetric all-solid-state supercapacitors
[0132] DMSO-potassium ion intercalated Ti3C2 (DK-Ti3C2) was used as the negative electrode material, manganese dioxide coated DK-Ti3C2 (MnO2@DK-Ti3C2) was used as the positive electrode material, and Li 5.6 PS 4.6 Cl 1.4 As a solid electrolyte, the specific production process is as follows:
[0133] Step 1: Preparation of MnO2@DK-Ti3C2 positive electrode sheet
[0134] MnO2@DK-Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet;
[0135] Step 2: Preparation of DK-Ti3C2 negative electrode sheet
[0136] The DK-Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a negative electrode sheet;
[0137] Step 3: Preparation of solid electrolyte
[0138] Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and DK-Ti3C2 was added as an additive, wherein the DK-Ti3C2 accounted for 25% of the total mass of Li2S, P2S5, and LiCl, and the mixture was sintered in a vacuum furnace at 500°C for 5h. After cooling, Li with DK-Ti3C2 as an additive was obtained. 5.6 PS 4.6 Cl 1.4 Solid electrolytes;
[0139] Step 4: Assembly of asymmetric all-solid-state supercapacitor
[0140] The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor.
[0141] Comparative Example 3
[0142] (1) Preparation of Ti3C2
[0143] 1g of the precursor Ti3AlC2 powder was dissolved in 20mL of a HCl / NH4F mixed solution, wherein the molar ratio of HCl to NH4F in the HCl / NH4F mixed solution was 3:2 and the concentration of HCl was 9mol·L -1 , and at 60°C, at 400 rpm·min -1 The suspension was stirred at a stirring speed of 3000 rpm·min for 24 h. -1 The suspension was centrifuged at a centrifugal speed of , and then washed with deionized water until the pH value of the suspension was 7, vacuum filtered, and dried to obtain Ti3C2;
[0144] (2) Preparation of potassium ion intercalated Ti3C2:
[0145] Weigh 1g of Ti3C2 obtained in step (1) and dissolve it in 30mL of 3mol·L -1 KOH solution at 60°C and 400 rpm -1 The suspension was stirred at a stirring speed of 3000 rpm·min for 6 h. -1The suspension was centrifuged at a centrifugal speed of 10000 nm, and then washed with deionized water until the pH value of the suspension was 7. After vacuum filtration, the suspension was dried to obtain Ti3C2 and potassium ion intercalated Ti3C2 (K-Ti3C2).
[0146] (3) Preparation of MnO2-coated K-Ti3C2
[0147] Weigh 1 g of the potassium ion intercalated Ti3C2 obtained in step (2) and dissolve it in 20 mL of 0.5 M KMnO4 solution. The mixed solution is reacted at 150 °C for 5 h and then heated at 3000 rpm. -1 The suspension was washed with deionized water until the pH value of the suspension was 7, and the suspension was washed until transparent, and dried at 80°C for 12h to obtain manganese dioxide-coated K-Ti3C2 (MnO2@K-Ti3C2) powder;
[0148] (4) Assembly of MXene-based asymmetric all-solid-state supercapacitors
[0149] MnO2@K-Ti3C2 was used as the positive electrode material, K-Ti3C2 was used as the negative electrode material, and Li 5.6 PS 4.6 Cl 1.4 As a solid electrolyte;
[0150] Step 1: Preparation of MnO2@K-Ti3C2 positive electrode
[0151] MnO2@K-Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet;
[0152] Step 2: Preparation of K-Ti3C2 negative electrode
[0153] The K-Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and NMP was added and stirred to form a slurry. The slurry was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain the negative electrode. The CV test results are shown in Figure 8 Shown
[0154] Step 3: Preparation of solid electrolyte
[0155] Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and sintered in a vacuum furnace at 500°C for 5 h. After cooling, Li 5.6 PS 4.6 Cl 1.4 Solid electrolytes;
[0156] Step 4: Assembly of Solid-State Supercapacitor
[0157] The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor.
[0158] Figure 8 The CV test results of K-Ti3C2 without DMSO intercalation in Example 3 show that the energy stored in it is very small at high current density, and there is a capacitance decay rate of 15.8% during the charge and discharge process of only 15 cycles, indicating that the intercalation of DMSO has a great influence on the rate performance and long cycle performance of the electrode material.
[0159] In summary, in Example 1, MnO2@DK-Ti3C2 and DK-Ti3C2 are used as positive and negative electrode materials of asymmetric all-solid-state supercapacitors, respectively, and Fig. 9 The assembled asymmetric all-solid-state supercapacitor has good electrochemical properties and application prospects.
Claims
1. A method for preparing a MXene-based all-solid-state supercapacitor electrode material, characterized in that: The following steps are involved: (1) Preparation of Ti3C2 The precursor Ti3AlC2 powder is placed in a HCl / NH4F mixed solution and magnetically stirred at 50-70°C for 12-24h. The suspension after the reaction is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain Ti3C2. (2) Preparation of potassium ion intercalated Ti3C2 The Ti3C2 obtained in step (1) is dissolved in a KOH solution and stirred at 60-70°C for 5-8 hours. The obtained suspension is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain potassium ion intercalated Ti3C2. (3) Preparation of DMSO-potassium ion intercalated Ti3C2 The potassium ion intercalated Ti3C2 obtained in step (2) is mixed with DMSO, and stirred at 60-70°C for 3-5 hours. The obtained suspension is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain DMSO-potassium ion intercalated Ti3C2; (4) Preparation of MnO2@DK-Ti3C2 The DMSO-potassium ion intercalated Ti3C2 obtained in step (3) is dissolved in a 0.1-0.5M KMnO4 solution, and the mixed solution is reacted at 120-180°C for 5 hours. The suspension after the reaction is centrifuged, washed with deionized water, vacuum filtered, and dried to obtain a manganese dioxide-coated DMSO-potassium ion intercalated Ti3C2 powder.
2. The method for preparing a MXene-based all-solid-state supercapacitor electrode material according to claim 1, characterized in that: Step (1) The molar ratio of HCl to NH4F in the HCl / NH4F mixed solution is 3:2, and the concentration of HCl is 8 mol·L -1 ~10mol·L -1 The mass volume ratio of the precursor Ti3AlC2 and the HCl / NH4F mixed solution is 1:20 g·mL -1 .
3. The method for preparing a MXene-based all-solid-state supercapacitor electrode material according to claim 1, characterized in that: Step (1) The speed of magnetic stirring is 300-500 rpm·min -1 , centrifugal speed is 3000~4000rpm·min -1 , washing with deionized water until the pH value of the suspension is 6-7; step (2) the speed of magnetic stirring is 300-500 rpm·min -1 , washed with deionized water until the pH of the suspension is 6-7, and the centrifugal speed is 3000-4000 rpm·min -1 ; Step (3) The speed of magnetic stirring is 300-500 rpm·min -1 , washing with deionized water for 6 to 7 times until the suspension becomes transparent, and the centrifugal speed is 3000 to 4000 rpm min -1 In step (4), the centrifugal speed is 3000-4000 rpm·min -1 , wash with deionized water until the pH of the suspension is 6-7, wash the suspension until it is transparent, dry at 60-80°C, and dry for 8-12h.
4. The method for preparing a MXene-based all-solid-state supercapacitor electrode material according to claim 1, characterized in that: The concentration of the KOH solution is 2 mol·L -1 ~3mol·L -1 The mass volume ratio of Ti3C2 to KOH solution is 1:30 g·mL -1 .
5. The method for preparing a MXene-based all-solid-state supercapacitor electrode material according to claim 1, characterized in that: The mass volume ratio of potassium ion intercalated Ti3C2 and DMSO is 1:20g / mL.
6. The method for preparing a MXene-based all-solid-state supercapacitor electrode material according to claim 1, characterized in that: The concentration of KMnO4 is 0.1-0.5M, and the mass volume ratio of DMSO-potassium ion intercalated Ti3C2 to KMnO4 solution is 1:20g·mL -1 .
7. Use of the MXene-based all-solid-state supercapacitor electrode material prepared by the preparation method as claimed in claim 1 as an all-solid-state supercapacitor electrolyte additive and electrode material.
8. The use according to claim 7, characterized in that: DMSO-potassium ion intercalated Ti3C2 is used as an electrolyte additive for all-solid-state supercapacitors, and its addition amount accounts for 20% of the total mass of the electrolyte.
9. The use according to claim 7, characterized in that: The specific steps are as follows: (1) Preparation of positive electrode Manganese dioxide-coated DMSO-potassium ion intercalated Ti3C2 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a positive electrode sheet; (2) Preparation of negative electrode The DMSO-potassium ion intercalated Ti3C2 electrode material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, NMP was added dropwise and stirred to form a slurry, which was evenly coated on the surface of the carbon cloth, rolled flat, and dried at 80°C for 8h to obtain a negative electrode sheet; (3) Preparation of solid electrolyte Li2S, P2S5, and LiCl were mixed and ground in a molar ratio of 4.2:1:2, and DMSO-potassium ion intercalated Ti3C2 was added as an additive, wherein the DMSO-potassium ion intercalated Ti3C2 accounted for 25% of the total mass of Li2S, P2S5, and LiCl, and the mixture was sintered in a vacuum furnace at 500°C for 5h. After cooling, Li with DK-Ti3C2 as an additive was obtained. 5.6 PS 4.6 Cl 1.4 Solid electrolytes; (4) Assembly of asymmetric all-solid-state supercapacitors The positive electrode sheet, the negative electrode sheet and the solid electrolyte are assembled into an asymmetric all-solid-state supercapacitor.
Citation Information
Patent Citations
Preparation method of MnO<2> / Ti<3>C<2>T<x>Mxene flexible supercapacitor electrode material
CN108807003A
MnO2 / MXene / CC flexible composite electrode material and preparation method thereof
CN110136986A